Protocol of Whey Protein Isolate–Based Microgel Targeted Delivery in Mouse Kidney - Oksana Mayorova; Mariia Saveleva; Daria Terentyeva; Olga Gusliakova; Olga Sindeeva (Bio-Protocol)
Every year, there is an increase in the number of cases of chronic kidney disease, and a delay in the initiation of adequate treatment can lead to kidney failure, which requires regular dialysis or transplantation. Intensive systemic therapy used to treat kidney diseases often has a negative impact on other weakened organs, making it crucial to ensure targeted delivery of medications directly to the kidneys and to minimize systemic side effects. In order to reduce the toxicity of medications and decrease dosages, innovative delivery methods are being developed, such as micro-sized targeted delivery systems, which ensure highly effective distribution of encapsulated drugs directly within the organs. In a recent article, we presented innovative emulsified microgels stabilized with whey protein isolate (WPI), specifically designed for targeted drug delivery to the kidneys. Our stability studies revealed that these microgels start to degrade after 72 h, with this degradation exhibiting a time-dependent profile. Furthermore, intravenous administration of the microgel suspension through the tail vein showed significant selective accumulation in both the liver and kidneys over a duration of 5 days. As part of our research, we present the protocol for synthesizing emulsion microgels derived from whey protein isolate. This article provides a comprehensive overview of the procedures for precursor preparation, along with an in-depth investigation of the emulsion system's stability over time. The protocol also includes the injection of an emulsion microgel suspension into the tail vein of mice, enabling the evaluation of their biocompatibility and potential therapeutic efficacy. This protocol outlines the precautions and important nuances that should be considered at each stage of the experiment.